Relevansi Pendidikan Kritis Paulo Freire dengan Pendidikan Islam - Ainul Yaqin (Tarbiyatuna: Jurnal Pendidikan Islam, 2015)
Criticisms which always come up in Islamic Education is a doctrinal, dogmatic learning model that gives no freedom to learners. It is theoretically on the basis of the epistemology of Paulo Friere on oppressed people. According to him the oppressed people who internalize themselves with those oppressing them and adapted themselves with their way of thinking will bring a feeling of severe threat. Islam prioritizes mankind, upholds democratic values and justice, appreciates what men have done, teaches people how to speak truly and behave properly, and loves the week and the oppressed. It is in this position that freedom fits those values.